ANALISIS STRATEGI DIVERSIFIKASI BISNIS (STUDI KASUS PT SUN STAR MOTOR GROUP) - Edon Ramdani (LPPM Universitas Putera Batam, 2018)
To realize the vision and mision of PT Sun Motor Group to be the leading company and to create stakeholders value, it needs the right strategy for the company to grow and compete in the long term (competitive sustainable adventage). As a part of the automotive players in Indonesia, PT Sun Motor Group determined to become a major player in the automotive industry, but with the development of business world PT Sun Motor Group deems it necessary to enter the field of another industry that have a very good growth rate and then entering the property and hotels industry. This paper aims to analyze the strategy implemented and already appropriate strategy to support business growth of PT Sun Motor Group. Based on the results of the analysis that has been done can be concluded that the strategy has been implemented is quite appropriate and proven to enhance shareholder value. However, in line with the development of the business world, the influence of macro and micro economics, then it must continually evaluate this strategy to adapt the growth of business and to continue to enhance shareholder value.